Knowledge process capabilities and innovation: testing the moderating effects of environmental dynamism and strategic flexibility - Yozgat, Uğur; Kamaşak, Rifat; Yozgat, Uğur; Yavuz, Meltem (Palgrave Macmillan Ltd, Brunel Rd Bldg, Houndmills, Basingstoke Rg21 6Xs, Hants, England, 2017)
Knowledge process capabilities are highly associated with innovation performance. Namely, firms which develop better capabilities in processing knowledge can innovate better. The Dynamic Capabilities view states that the effects of contextual variables on capability development cannot be ignored. This study seeks to examine the roles of two contextual variables; environmental dynamism and strategic flexibility on developing knowledge process capabilities and innovation performance. In parallel with this aim, a survey was conducted on a sample of 236 firms from different industries in Turkey and a number of hypotheses including the interaction effects of environmental dynamism and strategic flexibility were tested through moderated multiple regression methods. The three-way interaction of knowledge process capabilities, environmental dynamism and strategic flexibility was associated more strongly with innovation performance than the two-way interactions of knowledge process capabilities and environmental dynamism, and knowledge process capabilities and strategic flexibility. Hence, the findings revealed that the effectiveness of knowledge process capabilities on the way of enhancing innovation performance in highly dynamic markets were contingent upon strategic flexibility.
Keywords: Knowledge process capabilities; Environmental dynamism; Strategic flexibility; Innovation performance; Resource-Based View; Product Development; Organizational Capabilities; Firm Performance; Research Agenda; Management; Industry; Complexity; Rigidity; Breadth